Teacher Talk as Pedagogical and Moral Discourse in Indonesian Rural Islamic Schools. - Cut Raudhatul Miski; Syahrul Ramadhan; Yuli Tiarina (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study examines the role of teachers' speech acts as both a learning discourse and a medium for instilling moral values ​​in rural Islamic schools in Indonesia through the integration of the IRF (Initiation–Response–Feedback) framework and Islamic communication principles (Qaulan). Using a qualitative descriptive design, data were collected through lesson recordings, classroom observations, and interviews with three teachers. The results indicate that classroom interactions are still dominated by the initiation stage, while student responses are brief and reactive, and teacher feedback is more evaluative than elaborative. Nevertheless, teacher talk consistently reflects Islamic communication values ​​such as qaulan ma'rufan, qaulan layyinan, qaulan baligha, and qaulan sadidan through polite speech, clear instructions, and positive reinforcement that support student character development. The significance of this study lies in its contribution to enriching understanding of how classroom discourse in rural Islamic schools combines pedagogical and moral functions. These findings fill a research gap on the implementation of Islamic values ​​in verbal classroom interactions and offer practical recommendations for improving teacher communication through the use of higher-order questions and elaborative feedback. This research is crucial for fostering more dialogic, inclusive, and meaningful learning in Islamic schools in rural contexts.